SYSTEMATIC LITERATURE REVIEW PENGARUH EMPLOYEE RETENTION DAN TURNOVER INTENTION TERHADAP KINERJA KARYAWAN - Bara Fadihila Haly; Laela Rahmaniya Marzukoh; Talisha Piknadia Ivanka; Dani Rizana (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to analyze the influence of employee retention and turnover intention on employee performance using a Systematic Literature Review (SLR) approach. Employee retention, as a strategy to retain talent within an organization, and turnover intention, which reflects an employee’s desire to leave, are critical factors that directly impact organizational productivity and performance. This research synthesizes findings from scholarly articles published in indexed journals over a specific period. The results reveal that effective employee retention strategies positively influence employee performance, while turnover intention has a negative effect. Factors such as organizational culture, leadership style, job satisfaction, and employee engagement are identified as significant mediators in the relationship between these variables. The study provides practical recommendations for organizations to enhance employee retention and reduce turnover intention through robust policies, professional development programs, and fostering a positive work environment. This study contributes to a deeper understanding of how these dynamics affect employee performance, offering both theoretical and practical insights.